High expression of RARG accelerates ovarian cancer progression by regulating cell proliferation - Xiu, Lin; Zhao, Yuxi; Li, Ning; Zeng, Jia; Liu, Jing; Fu, Yongliang; Gao, Qiao; Wu, Lingying (Frontiers in Oncology, 2022)
Purpose: To explore the relationship between retinoic acid receptor gamma (RARG) and ovarian cancer (OC) cell proliferation and the prognosis of patients. Methods: The transcriptome and clinical information of 379 OC and 88 normal ovarian samples were downloaded from the Cancer Genome Atlas (TCGA) database and the Genotype Tissue Expression (GTEx) database. We compared the mRNA level of RARG between ovrian normal and tumor tissues with the Wilcoxon rank sum test.The R package “limma” was used to analyze the differences in RARG expression between different clinical subgroups. Kaplan‒Meier analysis was applied to evaluate the correlation between RARG and prognosis of patients. A nomogram was established to predict the effect of RARG on prognosis of OC patients. Immunohistochemistry and qRT‒PCR experiments were conducted to determine the differential expression of RARG between ovarian normal and tumor tissues. Finally, we altered RARG expression using specific siRNA and lentiviral expression vectors to explore the function of RARG by CCK-8, cell cycle, colony formation, and xenograft assays in nude mice. Results: RARG was highly expressed in ovarian tumors and was an independent predictor of poor overall survival outcomes. Subgroup analysis showed the high expression of RARG was related to FIGO stage III-IV (P=0.027), overall survival time <5 years (P=0.013) and dead status (P=0.041). The Kaplan-Meier curve indicated that patients with high RARG expression level had poor prognosis. The area under the curve (AUC) of RAGR expression for predicting patient survival rates at 1, 5 and 9 years were 0.659, 0.616 and 0.627, respectively. The GSEA enrichment analysis revealed that RARG was involved in ovarian cancer progression through multiple pathways. In cellular experiments in vitro, downregulation of RARG expression significantly suppressed the proliferation and colony formation capacity of OC cells. In cellular experiments in vivo, knockdown of RARG significantly reduced tumor growth in nude mice, decreased expression levels of Ki-67 and proliferation cell nuclear antigen (PCNA). Conclusions: High expression of RARG could promote OC cell proliferation and was an independent predictor of poor prognosis. RARG might work as a potential molecular target and biomarker for individualized diagnosis and treatment in OC patients.